Synthesis and characterization of sulfonated carbon catalysts derived from biomass waste and its evaluation in glycerol acetylation - Nda-Umar, Usman Idris; Ramli, Irmawati; Muhamad, Ernee Noryana; Azri, Norsahida (Springer, 2022)
Sulfonated carbon catalysts were synthesized from palm kernel shell biomass using direct, chemical and template methods of carbonization under CO2 environment at 400 and 800 °C respectively and subsequently functionalized with concentrated sulfuric acid. The precursor material and the synthesized catalysts were characterized by proximate analysis, CHNS, XRD, FTIR, TPD, TGA, SEM, N2 adsorption isotherm, BET surface area, and acid-base titration. The synthesized acid catalysts were evaluated in glycerol acetylation with acetic acid (molar ratio 1:6) in a batch liquid phase reaction under atmospheric pressure at 120 °C, 450 rpm for 1 h, 3 h, and 5 h respectively. The performance was compared with commercial Amberlyst-15 catalysts and homogeneous concentrated sulfuric acid. Of all the synthesized catalysts, the catalyst obtained from the template method carbonized at 800 °C showed the highest selectivity to triacetin (58.9%) with over 97% glycerol conversion within a 3-h reaction time. The selectivity to monoacetin and diacetin was 5.8 and 32.2% respectively. The catalytic activity of the catalyst was attributed to the synergistic effect of good physicochemical characteristics including textural properties and high acidic site density.